Research trends related to the role of artificial intelligence in improving blended learning practices at the undergraduate level - Aldossari, Ghzail Fahad; Al-Dosari, Sarah Misha'i (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify research trends related to the role of artificial intelligence (AI) in improving blended learning practices at the undergraduate level, in the context of the Kingdom's Vision 2030, which focuses on digital transformation and enhancing the quality of education. The study focused on blended learning as a leading educational model that combines traditional and digital learning, while analyzing how AI technologies, such as adaptive systems and data analytics, can be employed to design personalized educational content that meets the diverse needs of students. The study relied on a descriptive-analytical approach by analyzing 20 previous studies related to the research topic. These studies were categorized into categories that addressed education personalization, content design improvement, and the use of the Technology Acceptance Model (TAM) to analyze user acceptance of smart systems. The most important results showed that blended learning enhances academic achievement by combining technological flexibility with personalized interaction, while AI technologies contribute to improving the quality of blended learning by providing personalized learning paths, immediate support, and effective student performance analysis. The results also pointed to challenges including a lack of digital infrastructure and weak technical proficiency among users. Accordingly, the most important recommendations were the need to invest in developing digital infrastructure, offering specialized training programs for teachers, and enhancing student awareness of the educational benefits of artificial intelligence. The study also proposed strategic partnerships between universities and technology institutions. The study also called for the development of policies that protect data privacy and guide the use of AI technologies in education to achieve the goals of Vision 2030.
Keywords: Artificial Intelligence; Blended Learning